Apropriação e domínio de instrumentos para o ensino de astronomia - Leonardo Marques Soares (2010)
The present research sought information on how teachers appropriate and create their dominion over the instruments of the KIT FOR THE TEACHING OF ASTRONOMY (KITPEA). The subjects of this study were teachers who attended the course on astronomy education offered bythe Continuing Education Project (FoCo) at the Center for Teaching Science and Mathematics (CECIMIG), Faculty of Education, Federal University of Minas Gerais (FAE / UFMG ). We have collected data through a questionnaire and an interview with these teachers. We structured thedata analysis with the help of Activity Theory and the Theory of Mediated Action. We have applied a interpretive discourse analysis of the teachers statements using as the analytical device the constitutive elements of the activity system and the concepts of appropriation and dominion.In this research appropriation means "taking something from other and making it your own" and the dominion means "knowing how to use a cultural tool." We consider as appropriate instruments, those which teachers reported some usind during a learning activity. The dominion,by its turn, we interpreted as the way teachers described the adaptations of the instruments in their activities, and how they have overcome the difficulties encountered. From our analysis we identify other ways for teachers to continue the process of training in the field of astronomyeducation such as visits to observatories, participation in study groups, reading periodics. Among the 11 subjects who participated in the survey, it was possible to interpret clearly the field in seven narratives. In summary, we recommend that teachers initially have the opportunity to learn the tools of KITPEA, then adapts them to the development of activities with their students. We also recommend the development of activities involving more subjects of the school community,so they can help each other overcome the difficulties which usually appear during the use of instruments KITPEA.